Change of Lithium concentration in Cedrus atlantica and Pseudotsuga menziesii tissues in the higher air-polluted areas - Halil Baris OZEL; Hakan SEVIK; Vedat KARACAN (GSC Online Press, 2023)
Heavy metal pollution is today's most critical pollution element, threatening the atmosphere and health. Lithium (Li), a heavy metal, has recently been extensively used in various industrial areas and poses a risk to environmental health, including human health. It is well-known that heavy metals can be much more harmful when taken into the human tissues via inhalation. Therefore, tracking and decreasing the alteration in Li contamination in the airborne is essential. The current study aimed to define whether Pseudotsuga menziesii and Cedrus atlantica are suitable for monitoring and reducing Li pollution in the air. Within the scope of the study, variations in Li concentration depending on organ, direction, and age range in the last 40 years were evaluated in Pseudotsuga menziesii and Cedrus atlantica species growing in Düzce, Türkiye, which is amongst the 5 most contaminated provinces in Europe. As a result, it was determined that Li pollution in the region was of anthropogenic origin and that both species were suitable for monitoring Li pollution but were not suitable for use in reducing it.
Keywords: contamination; Heavy metal; Toxicity; Biomonitoring; Düzce; 13. Climate action; 3. Good health